NEW ALGORITHM FOR INVERSION OF GRAVITATIONAL DATA - Gryshchuk, P. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the description of the new algorithm for inversion of gravitational anomalies.The principle of the geological objects mass displacement is used for definition of its geometry. In the grid model, the movement of blocks is performed in four directions for a two-dimensional model. The motion and changing of density is determined in a random style. This algorithm defined the geometry of three rectangular bodies of model. The conditions for determining the exact form of gravity sources by the proposed approach were clarified. An analysis of the inversion of gravity acceleration anomalies from three bodies for sections, which consisted of three, four and five layers, was performed. The bodies of identical density were determined exactly for three and four layers, and with errors for the five layers. The model with two densities had some errors in determining the geometry of the bodies. Scientific novelty is related to the development of new algorithm, which is based on the principle of moving for density between blocks. The new approach fulfils gravity inversion much faster than the genetic algorithm. The practical significance is determination of the number of layers needed for a proper inversion of gravity anomalies. The main factors influencing the accuracy of geometry are the data of body density and the number of layers. The method was used for the interpretation of gravity data over the coal deposits of the Donbas. The model consisted of five layers and a range of minimum to their maximum densities for the geological section. Data of the inversion was determined by the depth to the surface of the limestone, which is confirmed by the data of the drilling. The developed approach determines the geometry of section from density, which is important for geological, search and environmental tasks.
Keywords: gravitational inversion; number of layers of the model; mass movement algorithm; inversion accuracy; genetic algorithm; coal layers of the Donbas